IDEA COMMERCIALISATION: MALAYSIA RANKS SIXTH IN THE WORLD - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 8 December 2015 – Malaysia is ranked sixth in the world for idea commercialisation efforts as the result of consultations, training, publications and other such efforts.